Endometrial Ablation for Heavy Menstrual Bleeding. (January 2016) - Kumar, Vinod; Chodankar, Rohan; Gupta, Janesh Kumar
Endometrial ablation can be described as one of the great gynecological success stories. It has changed the management of heavy menstrual bleeding dramatically. The development of newer (second generation) endometrial ablative techniques has enabled clinicians to set up comprehensive 'one stop clinics' based on an outpatient service to treat heavy menstrual bleeding effectively without the need for general anesthetic or conscious sedation. This article describes the rationale and evidence for use of different endometrial auto-ablative systems along with relevant technical and clinical aspects. It also addresses the essentials of a successful approach to outpatient endometrial ablation along with discussion on risks, complications and contraindications of the procedure.